X-ray diffraction studies of the growth process of thin films of high-entropy TiNbZrTaHfCu alloy in situ using synchrotron radiation - Yu.F. Ivanov; Yu.Kh. Akhmadeev; A.A. Klopotov; N.A. Prokopenko; E.A. Petrikova; O.V. Krysina; V.V. Shugurov; A.N. Shmakov; V.Yu. Lavrov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
High-entropy alloys based on refractory metals, possessing an unusual combination of physical, mechanical, tribological, electrophysical, etc. properties, can be recommended for use in various fields of industry and medicine. The aim of the work is to study the growth process of high-entropy alloys films of the Ti-Nb-Zr-Ta-Hf-Cu system in real time by X-ray phase analysis using synchrotron radiation. Experiments on the deposition of multielement metal films were carried out on the VEIPS-1 setup developed at the Institute of high current electronics Siberian branch of the Russian academy of sciences for studying the processes of the film and coating formation on a synchrotron radiation source. The process of in situ thin film structure formation with high time resolution was studied using a synchrotron radiation source – the VEPP-3 electron storage ring, the Institute of nuclear physics, Siberian branch of the Russian academy of sciences. It is shown that the deposition of Ti-Nb-Zr-Ta-Hf-Cu plasma on a HG40 substrate is accompanied by the formation of an amorphous-crystalline state represented by phases of the composition (presumably) Ti-Nb-Zr-Ta-Hf-Cu, TiZr, NbZr, and CuTiZr, formed at different stages of film deposition. The main phase is the Ti-Nb-Zr-Ta-Hf-Cu composition.